Implementation of CRM Applications in Social Programs BMT Insan Mandiri - Jamil, Muh; Alam, Syamsu; Asdaq, Muhammad; Taufik, Muhammad (PINISI Discretion Review, 2023)
This research is focused on evaluating the effectiveness of a customer relationship management (CRM) application, specifically tailored for XL-based customers, in enhancing the operational efficiency of the BMT Insan Mandiri social program. The study employs a descriptive qualitative analysis to delve deeply into how the application influences data management, interpretation, and strategic decision-making processes within the organization. The primary aim is to assess whether the CRM tool significantly improves the organization's ability to manage customer data, which is crucial for tailored communication and service delivery. By analyzing user interactions, feedback, and engagement within the CRM system, the study provides insights into how effectively the application streamlines data handling and facilitates a more personalized approach to customer relations. Furthermore, the research explores the application's role in aiding the BMT Insan Mandiri program to interpret customer data accurately. This aspect is vital for understanding customer needs and preferences, which can then be used to formulate more effective and targeted social program strategies. Additionally, the study examines the impact of the CRM application on strategic planning. This includes evaluating how the application assists in formulating strategic steps that align with the organization’s goals and customer expectations, thereby enhancing the overall efficacy of the BMT Insan Mandiri social program.